Analisis Kewajiban Para Pihak Dalam Perjanjian Sewa Menyewa Rumah Tinggal - Siregar, Michael Alpray; Sinaga, Elsa Nurhayati Roulinta; Siagian, Natanael Robona Asimi; Rafli, Ananda; S, Surahmad (Media Hukum Indonesia (MHI), 2024)
Rental housing agreements are a common form of transaction in communities. This article aims to analyze the obligations of the parties to the rental agreement to rent dwellings, both on the tenant and owner's side. The method used in this study is normative law research or library law research. Owner's obligations include provision of livable housing, maintenance of facilities, and compliance with applicable legal provisions. On the other hand, the tenant's obligations include timely rent payment, maintaining the conditions of the house, and complying with the conditions agreed upon in the contract. The study also found that violations of these obligations could lead to legal disputes, making it important for both parties to understand their rights and obligations clearly.